IL‐1β induces hypomyelination in the periventricular white matter through inhibition of oligodendrocyte progenitor cell maturation via FYN/MEK/ERK signaling pathway in septic neonatal rats. Issue 4 (17th December 2015) - Xie, Di; Shen, Fengcai; He, Shaoru; Chen, Mengmeng; Han, Qianpeng; Fang, Ming; Zeng, Hongke; Chen, Chunbo; Deng, Yiyu
Abstract : Neuroinflammation elicited by microglia plays a key role in periventricular white matter (PWM) damage (PWMD) induced by infectious exposure. This study aimed to determine if microglia‐derived interleukin‐1β (IL‐1β) would induce hypomyelination through suppression of maturation of oligodendrocyte progenitor cells (OPCs) in the developing PWM. Sprague‐Dawley rats (1‐day old) were injected with lipopolysaccharide (LPS) (1 mg/kg) intraperitoneally, following which upregulated expression of IL‐1β and IL‐1 receptor 1 (IL‐1R1 ) was observed. This was coupled with enhanced apoptosis and suppressed proliferation of OPCs in the PWM. The number of PDGFR‐α and NG2‐positive OPCs was significantly decreased in the PWM at 24 h and 3 days after injection of LPS, whereas it was increased at 14 days and 28 days. The protein expression of Olig1, Olig2, and Nkx2.2 was significantly reduced, and mRNA expression of Tcf4 and Axin2 was upregulated in the developing PWM after LPS injection. The expression of myelin basic protein (MBP) and 2', 3'‐cyclic‐nucleotide 3"‐phosphodiesterase (CNPase) was downregulated in the PWM at 14 days and 28 days after LPS injection; this was linked to reduction of the proportion of myelinated axons and thinner myelin sheath as revealed by electron microscopy. Primary cultured OPCs treated with IL‐1β showed the failure of maturation and proliferation. Furthermore, FYN/MEK/ERK signaling pathway was involved in suppression of maturation of primary OPCs induced by IL‐1β administration. Our results suggest that following LPS injection, microglia are activated and produce IL‐1β in the PWM in the neonatal rats. Excess IL‐1β inhibits the maturation of OPCs via suppression of FYN/MEK/ERK phosphorylation thereby leading to axonal hypomyelination. GLIA 2016;64:583–602 Main points: Microglial cells are activated and produce IL‐1β in the periventricular white matter in septic neonatal rats. Excess IL‐1β inhibits the maturation of OPCs via suppression of FYN/MEK/ERK phosphorylation thereby leading to axonal hypomyelination.